English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

how do you do this Pythagorean theorem math problem
b=12, c=13

2007-05-01 14:22:24 · 10 answers · asked by Anonymous in Science & Mathematics Mathematics

please work it out in steps i have alot of more problems to do all the others where a= and b= then i had to find c do i do this the same way

2007-05-01 14:26:53 · update #1

why do i subtract and in the others i add

2007-05-01 14:27:40 · update #2

10 answers

You add and subtract based on which variable you are solving for. If your variable is 'a' then you need to subtract both sides by 'b' in order to get 'a' by itself. Or, if you are solving for 'c' you just plug in 'a' and 'b'.

You basically need to get the variable you are solving for by itself, and to do that you need to subtract or add what is there.

Hope that helps!

2007-05-01 14:30:18 · answer #1 · answered by servinit2me 2 · 1 0

The Pythagorean Theorem:
a^2+b^2=c^2
a^2+12^2=13^2
a^2+144=169
a^2+144-144=169-144
a^2=25
a=5

2007-05-01 14:29:23 · answer #2 · answered by Anonymous · 1 0

a = 5

Since a^2 + 12^2 = 13^2, we know a^2 = 169 - 144 = 25 and therefore a = 5.

Of course, even though you use b and c in the givens, you could want "d." In that case, 12^2 + 13^2 = d^2 so: d^2 = 144 + 169 = 313 and d = 313^½.

But I will go with the idea that you want a = 5 since that is one of the basic Pythagorean Triples.


Added:

In all of them, you use the a^2 + b^2 = c^2 relationship. Because you are likely, as in this one, sometimes given c and one of a and b, you sometimes have to subtract. That is because you want to get all the numbers in the equation to one side, leaving the variable by itself (and then take the square root). In the ones that give you a and b, you add because the c is already by itself. That is why you sometimes subtract, sometimes add.

2007-05-01 14:25:21 · answer #3 · answered by roynburton 5 · 1 0

a^2 + b^2 = c^2

a^2 = 13^2 - 12^2
= 169 - 144
= 25
so a = 5

2007-05-01 14:26:18 · answer #4 · answered by looikk 4 · 1 0

a^2 + b^2 = c^2

plug in b and c
so you get a^2 + 12^2 = 13^2
subtract 144 on both sides

so it would be 169 - 144 = a^2

and then just square root

2007-05-01 14:29:09 · answer #5 · answered by v. 2 · 1 0

13^2-12^2=a^2
or 169-144=a^2
25=a^2
5=a

2007-05-01 14:26:01 · answer #6 · answered by bruinfan 7 · 1 0

square the thirteen and the twelve and subtract the answers from each other. Then you take the square ROOT of what you get.

2007-05-01 14:26:29 · answer #7 · answered by OrangeFuu 3 · 1 0

a=5
use the formula: C^2=A^2+B^2

2007-05-01 14:29:59 · answer #8 · answered by Anonymous · 1 0

a^2 + b^2 = c^2
plug in and solve for a

2007-05-01 14:27:07 · answer #9 · answered by Chow 2 · 1 0

a^+b^=c^
so.....

a^+12^=13^
a^+144=169
-144
a^=25
sq both sides
a=sqrt 25
a=5

2007-05-01 14:28:22 · answer #10 · answered by Anonymous · 1 0

fedest.com, questions and answers